Mobile Learning Improves Student Learning Outcomes in Mathematics Education - Dori Lukman Hakim (Journal for Lesson and Learning Studies, 2023)
The current problem is that interactive dialogue between educators and students is more challenging than face-to-face. It has an impact on low learning outcomes. The purpose of this study is to analyze the effect of the application of Mobile Learning (ML) on student learning outcomes, which will be seen based on student ability groups (High Category, Medium Category, Low Category), then based on each class (Class A, Class B, Class C), and overall students. This type of research is qualitative research with the One Sample Posttest Group Design. The sample for this study was 96 students from three classes which constituted the population and, at the same time, the sample in this study as a whole. The method used to collect data is a test. The instrument used to collect data is a math test sheet. The data analysis technique used in this research is descriptive qualitative analysis, quantitative and inferential statistics. The research results are that the influence of Mobile Learning (ML) on the student learning outcomes group for the high category does not give any influence. However, the student learning outcomes groups for the medium category and low categories do give an effect. The influence of Mobile Learning in each class, A, B, and C, shows a significant influence. The effect of Mobile Learning on student learning outcomes as a whole shows a significant influence. It was concluded that the application of mobile learning can have an impact on student learning outcomes.